REFLEKSI PENDIDIKAN LITERASI DALAM SURAT ALKAHFI AYAT 109 DAN RELEVANSINYA DI INDONESIA - Hadi Susilo (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2021)
In forming literate souls in students, it is not as easy as turning your palms. Therefore, through literate mental education, children will apply to their souls. Some of the methods used include the method of habituation, exemplary and so on.Now we see the level of Indonesian literacy research entitled World's Most Literate Nations Ranked, conducted by Central Connecticut State University, Indonesia is ranked 60th out of 61 countries regarding interest read. By exploring the verses of the Qur'an, Surat al-Kahf, verse 109, it will reveal an extraordinary literacy message that can be implemented in the world of education today. The role of educators in shaping a literate spirit is not only in conveying ways, but also by giving examples, and doing good habituation. The amount of knowledge, information, said Allah, requires a literate soul so that one can always seek the scientific information needed and according to what is desired.